The effects of A1/A2 astrocytes on oligodendrocyte linage cells against white matter injury under prolonged cerebral hypoperfusion. Issue 9 (28th February 2020) - Miyamoto, Nobukazu; Magami, Shunsuke; Inaba, Toshiki; Ueno, Yuji; Hira, Kenichiro; Kijima, Chikage; Nakajima, Sho; Yamashiro, Kazuo; Urabe, Takao; Hattori, Nobutaka
Abstract: As oligodendrocyte precursor cells (OPCs) are vulnerable to ischemia, their differentiation to oligodendrocytes (OLG) is impaired in chronic cerebral hypoperfusion. Astrocyte–OLG interaction is important for white matter homeostasis. Recently, reactive astrocytes were separated into two types, A1 (cytotoxic) and A2 (neurotrophic). However, their role in prolonged cerebral hypoperfusion remains unclear. We analyzed the effects of interaction between A1–A2 astrocytes and OPC–OLG under hypoperfusion, focusing on mitochondrial migration. As an in vivo model, chronic hypoperfusion model mice were created by bilateral common carotid artery stenosis (BCAS) using microcoils. As a matching in vitro study, rat primary cells were cocultured with a nonlethal concentration of CoCl2 . At 28 days after hypoperfusion, the number of OPC and astrocytes increased, whereas that of OLG decreased. Increased astrocytes were mainly A1‐like astrocytes; however, the number of A2‐like type decreased. In cell culture, OPC differentiation was interrupted under mimic chronic ischemia, but improved after astrocyte‐conditioned medium (ACM) was added. However, injured‐ACM was unable to improve OPC maturation. Incubation with CoCl2 changed astrocytes from A2‐like to A1‐like, and mitochondrial migration was also reduced. A Trkβ agonist was able to maintain astrocytes from A1‐like to A2‐like even under hyperperfused conditions, and aided in OPC maturation and memory impairment via mitochondrial migration and drug effects in cell culture study and BCAS model. The reduction of A1‐like astrocytes protects against white matter injury. Trkβ agonists may play an important role in the impairment under chronic ischemic conditions. Mitochondrial migration may be a broad therapeutic strategy for cerebrovascular diseases. Main points: Prolonged cerebral hypoperfusion leads to impaired oligodendrocyte (OLG) maturation and increased numbers of A1 astrocytes. Mitochondria migration maintained A2 astrocyte morphology, mature OLG, and myelinated white matter in vivo/vitro. Abstract : Schematic image for mitochondria interaction and Trkβ agonist treatment against prolonged cerebral hypoperfusion. Under normal conditions, astrocytes secrete mitochondria into oligodendrocyte linage cells to promote oligodendrocyte precursor cell (OPC) maturation. However, under prolonged cerebral hypoperfusion, mitochondria secretion from astrocytes decreased. As a result, white matter injury progressed due to reduced OPC maturation. Trkβ agonist treatment maintained A2‐like astrocytes even under hypoperfusion, and promoted astrocytic mitochondria secretion. Thus, OPC maturation was preserved and Trkβ agonists can protect against white matter damage.